Android-based Marketplace Application for Surakarta Local Products - Baronio, Nodas Constantine; Prasetyo, Sri Yulianto Joko (Politeknik Ganesha Medan, 2023)
During the Covid-19 pandemic, many companies suffered losses, leading to a reduction in employees and adversely affecting the community's economy. A significant portion of the local economy depends on the sale of locally produced goods. Moreover, the rapid advancement of information technology has intensified business competition, further impacting the development of local products. Unfortunately, the potential of information technology, particularly Marketplace platforms, to boost the economy and facilitate transactions between customers and sellers has been overlooked. To address these issues, this research aims to develop a Marketplace application to assist the community in selling and promoting their locally made products. The research involves several stages, including analysis, design, simulation prototyping, implementation, monitoring, and management. The result of this study is an Android-based Marketplace application designed to support the sale of local products.